ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PRESTASI MAHASISWA (Studi Kasus Pada Jurusan Administrasi Bisnis Politeknik Negeri Semarang) - Hadiahti - Utami; Siti Nur Barokah; Taviyastuti - Taviyastuti (Politeknik Negeri Semarang, 2018)
This study aims to identify internal factors and external factors that affect the GPA of the students of the Business Administration Department of Politeknik Negeri Semarang and analyze how the mechanism of these factors affect the GPA of the students of the Department of Business Administration. The results of this study is very important in identifying the factors that affect the GPA of the students of Business Administration Department and can contribute and input to the Business Administration Department of State Polytechnic of Semarang in improving the index of student achievement in the future through the factors that are very influential found in this research. The result of parallel regression analysis shows that internal factors (health, intelligence, interest and motivation, technique / way of learning) have positive and significant influence on student's GPA, while external factor (family, school / campus, community, environment) and insignificant to the student's GPA. But simultaneously all the variables studied significantly influenced the student's GPA. This means that the variables of internal factors (health, intelligence, interests and motivation, techniques / learning methods) and external factors (family, school / campus, community, neighborhood) are appropriate or appropriate variables to explain variations in the student's GPA.